Determinants of risk perception towards science and technology - Suerdem, A.K.; Gumus, B.; Unanoglu, M. (My University, 2013)
Public concerns over the risks and the benefits of new technological developments have intensified the need for accountability of scientists, engineers, industries and governments over the research and development process. This study examines how factors such as knowledge, trust, participation, familiarity with technology, worldviews and demographic variables affect the perceived risks and benefits of science and technology. For this purpose, we conducted regression analyses for the Eurobarometer Science and Technology survey which is a part of wave 73.1. Results suggest that trust to the authority of science is the main determinant of the perceived risk. © 2013 Taylor & Francis Group.
Society for Risk Analysis
4th International Conference on Risk Analysis and Crisis Response, RACR 2013 -- 27 August 2013 through 29 August 2013 -- Istanbul -- 100914
Keywords: Demographic Variables; Perceived Risk; Public Concern; Research And Development; Science And Technology; Technological Development; Intelligent Systems; Public Risks; Regression Analysis; Risk Analysis; Risk Perception; Technology